Cocoa on the Rise - Schulze Frenking, Tobias (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
The current situation of the cocoa industry is addressed, highlighting the importance of collaboration among the sector's stakeholders to face the challenges it faces, especially in the context of production in the Caribbean and the decline in cocoa exports. Despite these challenges, the Caribbean fine cocoa brand continues to be recognized and valued internationally. A forum was held where industry stakeholders shared knowledge and experiences, focusing on sustainable cocoa development in the region. Findings from co-financed cluster projects were presented, covering topics such as organic certification, permaculture practices and the use of biostimulants. The need to improve cocoa quality and tree health was highlighted as critical, especially in the face of the climate crisis and market volatility. Also, the importance of storytelling in cocoa marketing is emphasized, suggesting that a digital narrative can increase visibility and support for Trinidad and Tobago's cocoa industry.